2011
DOI: 10.1371/journal.pone.0025914
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses, Gene Expression and Antigenic Profile of the Trans-Sialidase Superfamily of Trypanosoma cruzi Reveal an Undetected Level of Complexity

Abstract: The protozoan parasite Trypanosoma cruzi is the etiologic agent of Chagas disease, a highly debilitating human pathology that affects millions of people in the Americas. The sequencing of this parasite's genome reveals that trans-sialidase/trans-sialidase-like (TcS), a polymorphic protein family known to be involved in several aspects of T. cruzi biology, is the largest T. cruzi gene family, encoding more than 1,400 genes. Despite the fact that four TcS groups are well characterized and only one of the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 59 publications
(71 reference statements)
4
113
0
11
Order By: Relevance
“…These UTRs could cause expression efficiency to differ between the various stages, with greater expression efficiency in the trypomastigote blood forms resulting from intracellular replication, although it has been recently shown that expression levels are not homogeneous among genes belonging to different groups of TSs (34,38).…”
mentioning
confidence: 99%
“…These UTRs could cause expression efficiency to differ between the various stages, with greater expression efficiency in the trypomastigote blood forms resulting from intracellular replication, although it has been recently shown that expression levels are not homogeneous among genes belonging to different groups of TSs (34,38).…”
mentioning
confidence: 99%
“…Células epiteliais de Macaca mulata da linhagem de LLC-MK2 (ATCC CCL-7) (macaco rhesus) foram utilizadas para o cultivo do T. cruzi e os ensaios de infecção. As células foram mantidas em meio mínimo essencial das gp85/trans-sialidases foram obtidas no banco de dados TriTrypDB (ASLETT et al, 2010) utilizando listas de genes publicadas por FREITAS et al (2011). As sequências pertencentes ao grupo II das gp85/trans-sialidases foram então alinhadas utilizando o software "Clustal Ômega" (SIEVERS et al, 2011).…”
Section: Methodsunclassified
“…Com base na similaridade de sequências, as proteínas codificadas por esta família de genes foram ainda subdivididas em oito grupos (FREITAS et al, 2011). As proteínas pertencentes ao grupo I são as únicas proteínas que possuem domínios trans-sialidase enzimaticamente ativos, podendo remover resíduos de ácido siálico das glicoproteínas presentes na superfície celular dos mamíferos e transferí-los para glicoproteínas na membrana celular do parasita.…”
Section: Introductionunclassified
“…A superfamília gp85/TS foi inicialmente dividida em quatro grupos de acordo com a presença de domínios ou motivos estruturais conservados (Asp Box, SAPA, VTxNVxLYNR, também denominado VTV ou FLY) (Pereira, et al, 1991, Colli, 1993, Cross & Takle, 1993, Frasch, 1994, Schenkman & Eichinger, 1994 Sayed, et al, 2005) e uma nova distribuição em 8 grupos foi proposta, sendo os grupos I a IV idênticos à distribuição anterior (Freitas, et al, 2011). O grupo I é o único formado por proteínas com atividade de trans-sialidase.…”
Section: Atuação Da Superfamília Gp85 /Trans-sialidases De T Cruziunclassified
“…Grupo II é constitudo pelas glicoproteínas localizadas na superfície do parasita, como Tc85. Grupo III apresenta as proteínas de superfície associadas ao flagelo do parasita e os demais grupos (IV a VIII) apresentam os membros cuja função ainda não foi evidenciada (Freitas, et al, 2011. Na análise desses oito novos grupos, 328…”
Section: Atuação Da Superfamília Gp85 /Trans-sialidases De T Cruziunclassified